2000
DOI: 10.1175/1520-0485(2000)030<1472:ottipf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

On the Tide-Induced Property Flux: Can It Be Locally Countergradient?*

Abstract: The horizontal property flux induced by tides is examined by both analytical and numerical models. It is found that this flux is highly heterogeneous in the vertical and may be directed up the mean gradient near the bottom. This countergradient tidal flux is a consequence of differing boundary conditions satisfied by velocity and property fields, and hence a robust feature. The corresponding tidal diffusivity is substantial where tides are strong and hence potentially important in the mean property balance.* L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…At sections A and C, the strongly tidal oscillatory salt transport occurs near the interface of the inflow layer and outflow layer. This is different from the structure caused by tidal shear dispersion, which is negative near boundaries and positive away from boundaries (Larsen 1977;Ou et al 2000;Bowen and Geyer 2003).…”
Section: B Mechanisms Of F T During Neap Tidementioning
confidence: 60%
See 1 more Smart Citation
“…At sections A and C, the strongly tidal oscillatory salt transport occurs near the interface of the inflow layer and outflow layer. This is different from the structure caused by tidal shear dispersion, which is negative near boundaries and positive away from boundaries (Larsen 1977;Ou et al 2000;Bowen and Geyer 2003).…”
Section: B Mechanisms Of F T During Neap Tidementioning
confidence: 60%
“…For the shear dispersion mechanism, the mixing perpendicular to the shear causes the phase shift between tidal velocity and salinity that vary through the cross section in such a way as to produce a net upstream salt transport (Larsen 1977;Ou et al 2000;Bowen and Geyer 2003). The phase shift is greater than 908 in the slow-moving fluid near boundaries and less than 908 away from boundaries, inducing negative tidal oscillatory salt transport near boundaries and positive tidal oscillatory salt transport away from boundaries (Fig.…”
Section: Mechanisms Of F T During Spring Tidementioning
confidence: 99%
“…Vertical tidal oscillatory shear dispersion results from the straining and vertical mixing of the salinity field by vertically sheared oscillatory tidal currents (Okubo 1967;Larsen 1977;Fischer et al 1979;Ou et al 2000). The longitudinal dispersion rate associated with tidal oscillatory shear dispersion is maximal when the tidal period matches the vertical mixing time scale.…”
Section: B Tidal Oscillatory Salt Fluxmentioning
confidence: 99%
“…The contour interval is 5 ϫ 10 Ϫ1 kg m Ϫ2 s Ϫ1 in (c) and 2 ϫ 10 Ϫ1 kg m spatial structure is consistent with tidal oscillatory shear dispersion. The flux near the bottom boundary layer is countergradient (negative) as a consequence of tidal currents near the bottom leading currents higher up in the water column (Larsen 1977;Ou et al 2000). The salt flux increases toward the surface where the tidal currents are stronger, and the area-integrated value is downgradient (positive).…”
mentioning
confidence: 99%
“…Ralston and Stacy [2005] discuss the importance of lateral circulation to salt flux and observed that dispersion due to vertical shear was a maximum during stratified ebbs. Larsen [1977] and Ou et al [2000] show the cross-sectional structure of shear dispersion, associating localized up-gradient tidal fluxes with bottom or side boundary layers in which the current phase leads the rest of the channel. Bowen and Geyer [2003] found shear dispersion responsible for three quarters of the tidal salt flux in a section of their modeled Hudson that had little along channel variation in bathymetry.…”
Section: Introductionmentioning
confidence: 99%